한국인의 흥을 매개체로 누가복음 10:17-24 읽기 - 안경순(AHN Kyung-Sun) (Changsin nondan, 2024)
본 연구는 한국인의 기쁨의 정서인 흥(興)을 매개체로 하여 누가복음 10장 17-24절 읽기를 시도한다. 누가복음 10장 17-24절은 사역을 마치고 돌아온 칠십 인의 제자들의 기쁨과 즐거움, 이로 인한 예수의 기쁨과 즐거움이 잘 표현되어 있어서 누가복음의 기쁨과 기쁨의 예수상에 대한 상관관계 유추가 가능하다. 또한 칠십 인의 제자들과 예수의 기쁨과 즐거움 안에서 누가복음 저자가 전하고자 하는 또 다른 의미를 파악할 수 있다. 이를 위해 한국학에서 정의하고 있는 흥의 개념, 본질과 특징을 근간으로 흥의 관계성, 긍정적 측면에 집중한다. 그리고 누가복음 10장 17-24절의 기쁨과 기쁨의 예수상에 대한 해석과 이해를 도모하며, 누가복음 저자가 누가공동체에게 전하고자 했던 것은 무엇이었는지에 대해 살펴본다. 이를 통해 한국인의 흥 안에서 예수와 제자들이 하나라는 일체감에서 오는 기쁨의 의미, 예수와의 관계를 통해 당시 로마제국의 가치와 사회질서에 대한 전복을 넘어, 존재의 대동성으로 나아가게 되는 누가공동체의 진정한 기쁨의 의미를 제시한다. 이와 같은 시도는 1세기 갈릴리의 유대인 예수와 이 땅의 현재 교회공동체를 통하여 자신의 역사를 지속하는 예수와의 간격을 메우는데 궁극적으로 기여하게 될 것이다. This paper examines Luke 10:17-24 through the lens of Heung—the Korean emotion of joy. The passage reveals a correlation between Luke’s portrayal of joy and Jesus’s joyful image, particularly through the elation of the seventy disciples returning from their ministry and Jesus own rejoicing. The disciples and Jesus shared joy reveals deeper meanings intended by Luke’s author. This study explores the relationship and positive aspects of Heung by examining its concept, essence, and characteristics in Korean studies. It seeks to interpret Jesus image in Luke 10:17-24 and understand the author’s ultimate message to the community. Through this analysis, the paper reveals how the unity between Jesus and his disciples creates a joy connected to salvation, reflecting the Korean concept of Heung. It also demonstrates how the Luke community’s true joy transcends the Roman Empire’s social order and values, achieving equality through their relationship with Jesus. This study helps bridge the gap between the contemporary church community’s continuing work of Jesus and the historical Jewish Jesus of first-century Galilee. KCI Citation Count: 0